Plant-insect interactions in the mid-Cretaceous paleotropical El Chango Lagerstätte (Cintalapa Fm., Mexico)—patterns of herbivory during the Angiosperm Terrestrial Revolution - Santos, Artai A.; McLoughlin, Stephen; Rubalcava-Knoth, Marco A.; Hernández-Damián, Ana L.; Villanueva-Amadoz, Uxue; Cevallos-Ferriz, Sergio R. S. (Frontiers in Ecology and Evolution, 2024)
Plants and insects are two of the more diverse and abundant organisms in terrestrial ecosystems. The fossil record of plant-insect interactions offers crucial insights into the coevolutionary dynamics between these groups, shedding light on the intricate relationships that have shaped terrestrial ecosystems. The study of fossil interactions is especially relevant in mid-Cretaceous ecosystems, a time of dramatic changes in the composition of floras and, consequently, in plant-insect relationships. Here, we describe the first suite of plant-insect interactions from the mid-Cretaceous of Mexico. We studied 554 plant fossils from the El Chango Lagerstätte (Cintalapa Formation, Chiapas, Mexico), including vegetative (leaves) and reproductive structures (fruits and seeds). The flora was dominated by gymnosperms (89.3%) followed by angiosperms (10.7%); other groups, such as pteridophytes and bryophytes, were absent. In total, 5.4% of the plant specimens hosted some damage. Angiosperms (all broad-leafed forms), despite being much less common than gymnosperms, expressed more evidence of damage by herbivores (35.6% of specimens damaged). In contrast, the narrow-leafed gymnosperms, the dominant group in the flora, hosted a much lower proportion of herbivory damage (1.8% of specimens damaged). The diversity of damage types (DTs) was relatively low: 14 DTs were identified, corresponding to seven FFGs, including margin feeding, hole feeding, surface feeding, piercing and sucking, oviposition, galling, and mining. Comparison with the other mid-Cretaceous plant-insect assemblages reveals a similar richness of DTs for angiosperms but a lower richness and diversity of DTs on gymnosperms from El Chango. These results indicate preferential herbivory on angiosperms (rather than on the available gymnosperms in the assemblage) by terrestrial arthropods during a period of major changes in the structure of terrestrial ecosystems. However, it is challenging to resolve whether this apparent preference is because insects particularly targeted angiosperms or if the herbivores simply targeted broad leaves in general, since most of the available gymnosperms from El Chango are scale-leafed forms.